A Survey of Blockchain and E-governance applications: Security and Privacy issues - et. al., Ohood M. AlMendah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a world full of e-services that provide speed of implementation and comfort to customers and users and provide high-luxury features, whether in the world of stock's trading or e-government systems or others. However, any system can suffer from serious challenges such as security and privacy issues, so the existing infrastructure of e-Governance paves the way for a powerful underlying technology. Using Blockchain technology is a strong option to secure platforms and services. Therefore, a new framework that integrates Blockchain into any platform is proposed, especially in Saudi Arabia. This paper surveys research related to Blockchain technology and developments of its witch cut across both public and private sectors. The adoption and integration of e-governance is linked as a key point towards smart applications in the smart environment is discussed. For the improvement and development of any country, there is a need to connect technology-based services and products. These are the main points of an intelligent environment with e-governance in any area. This work refers to these views of e-governance and online services.